2023
DOI: 10.1093/ndt/gfad078
|View full text |Cite
|
Sign up to set email alerts
|

The sodium glucose co-transporter 2 inhibitor dapagliflozin ameliorates the fluid-retaining effect of the endothelin A receptor antagonist zibotentan

Abstract: Background Endothelin A receptor antagonists (ETARA) slow chronic kidney disease (CKD) progression but their use is limited due to fluid retention and associated clinical risks. Sodium glucose cotransporter 2 inhibitors (SGLT2i) cause osmotic diuresis and improve clinical outcomes in CKD and heart failure. We hypothesized that co-administration of the SGLT2i dapagliflozin with the ETARA zibotentan would mitigate the fluid retention risk using hematocrit (Hct) and bodyweight as proxies for flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In addition, owing to the mild diuretic effects of dapagliflozin, ZENITH-CKD will assess combined treatment of zibotentan with dapagliflozin to further reduce potential risks of sodium retention and oedema, and maximize clinical applicability. Indeed, an experimental study in a rat model demonstrated that adding dapagliflozin to high-dose zibotentan reduced zibotentan-induced fluid retention [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, owing to the mild diuretic effects of dapagliflozin, ZENITH-CKD will assess combined treatment of zibotentan with dapagliflozin to further reduce potential risks of sodium retention and oedema, and maximize clinical applicability. Indeed, an experimental study in a rat model demonstrated that adding dapagliflozin to high-dose zibotentan reduced zibotentan-induced fluid retention [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of zibotentan and dapagliflozin represents a novel therapeutic option for CKD, owing to different and potentially complementary mechanisms of action. In an experimental rat study, we demonstrated that zibotentan-induced fluid retention was mitigated with combined zibotentan/dapagliflozin treatment which suggests that adding dapagliflozin to zibotentan may be an effective strategy to reduce fluid retention and maximize clinical utility of zibotentan [ 26 ]. Here, we report the design and baseline characteristics of the Zibotentan and Dapagliflozin for the Treatment of CKD (ZENITH-CKD) trial.…”
Section: Introductionmentioning
confidence: 99%
“…A post hoc analysis of SONAR showed that combined treatment with SGLTi and atrasentan versus atrasentan alone demonstrated decreased body weight, a surrogate endpoint for fluid retention, and further decreased albuminuria, mitigating risks and decreasing the risk of mortality, which is tightly linked to residual albuminuria [ 42 , 43 ]. Further experimental evidence confirmed that combining ET A receptor antagonists with SGLT2i attenuates ET A receptor antagonist–induced fluid retention in 4% in salt-fed WKY rats [ 44 ]. This was followed by the recently published ZENITH-CKD Phase 2b RCT comparing zibotentan, a potent and highly selective ET A antagonist, with placebo in diabetic and non-diabetic CKD patients [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 91%
“…The SGLT-2 transporter in humans, is thought to be mainly restricted to the renal proximal convoluted tubule, resulting in increased glucose excretion favouring improved glycaemic control in Type 2 Diabetes (T2DM) and diuresis. SGLT-2i co-therapy may reduce fluid retention observed with ET receptor antagonists, a mechanism of action demonstrated in an animal model using haematocrit and bodyweight [ 5 ]. In recent years, a wealth of evidence has accumulated for SGLT-2i and dramatic decreases in cardiovascular adverse event rates, independent of glycaemic status, resulting in landmark trials in heart failure [ 6 ].…”
Section: Introductionmentioning
confidence: 99%